Controversies in neuro-oncology - Wiegel, Thomas; Hinkelbein, Wolfgang 1948-; Brock, Mario 1938-; Hoell, Thomas 1961- (Frontiers of radiation therapy and oncology, 1999)
This volume brings together an interdisciplinary group of specialists to present and discuss the latest diagnostic and therapeutic concepts and current controversial issues in the management of primary and secondary brain tumors. In the first part, the latest technical developments in neuro-oncology are presented. These include the evaluation of positron-emission tomography for diagnosis, and neuronavigation and operative mapping for operation planning. Innovations in computer-assisted 3-D radiotherapy planning and in image fusioning of CT, MRT, SPECT and PET are also described. A large section of the book is devoted to the diagnosis and interdisciplinary treatment of glioblastoma, one of the most frequently occurring brain tumors. In-depth coverage is given to pathological differential diagnosis, operative standards and the results of radiotherapy. A detailed presentation of the current chemotherapeutic strategies as well as their evaluation within an interdisciplinary therapy concept is also provided. A special chapter focuses on the role of radiotherapy and neurosurgery in the treatment of craniopharyngioma. The final section features discussions on the therapeutic options for brain metastases. Individual indications for both whole-brain irradiation and radiosurgery are given and compared with neurosurgical intervention. New experimental chemotherapies are considered, and finally, the palliative use of chemotherapy is examined.In summary, this book provides an excellent survey of the state of the art in neuro-oncology. It is therefore recommended reading for all clinical neuropathologists, neurologists, neurosurgeons and radiation oncologists